The Implications Philosophy of Science on Metabolism Education and Kidney Failure Prevention: Building Students' Healthy Lifestyle - Preventing Kidney Failure Disease - Wahyuni, Diah; Nahadi, Nahadi; Anwar, Syaeful (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2025)
The philosophy of science serves as a framework for understanding and teaching scientific knowledge, including metabolism, to promote health and prevent chronic diseases such as kidney failure. This study aimed to explore students' perspectives on kidney failure among young adults and the implications of the philosophy of science in metabolism education. A qualitative case study approach was employed, involving six science education students in East Java. Data were collected through in-depth interviews and analyzed thematically. The findings reveal that students have positive experiences with metabolism education, enhancing their understanding of metabolic processes and their role in kidney health. The program also encourages lifestyle changes, such as increased healthy food consumption and physical activity. However, challenges such as limited access, academic stress, and inadequate facilities persist. Students demonstrate a high awareness of kidney failure, although some perceive their risk as low. This study highlights the importance of inclusive, community-based education approaches and the use of digital technology to amplify its impact.